KOMPETENSI DAN KOMITMEN MUTU KEPEMPINAN DALAM PEMBENTUKAN KARAKTER ISLAMI DI PESANTREN MODERN AS- SAKIENAH - Ebit Ibadurrokhman; Didin Nurul Rosidin; Asep Mulyana (CV. ADIBA AISHA AMIRA, 2025)
This study aims to analyse leadership competence and commitment in Islamic character building at As-Sakienah Modern Islamic Boarding School. A qualitative approach with a case study method was used to explore in depth the role of pesantren leadership. The results showed that, first, the leadership competence of education quality is very influential on Islamic character building. The pesantren leaders have the ability to monitor and foster santri, although monitoring needs to be done more thoroughly. Second, leadership commitment is reflected in the application of Islamic values, but consistency in its implementation still requires improvement to make character education more effective. Third, factors that influence leadership competence and commitment include the leaders' proactive approach in providing advice and the involvement of santri. The lack of santri participation in discussions shows the importance of creating a participatory environment to strengthen Islamic values. This study recommends increasing the consistency and active involvement of all elements of the pesantren in shaping a stronger Islamic character.